What next for the Economic Partnership Agreements? Thoughts on deepening the EU-Africa trade partnership - Clara Brandi; Merran Hulse; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Many actors in the G20, the EU and Germany are calling for a quantum leap in the economic co-operation between Europe and Africa. However current discussion of EU-Africa trading relations frequently focuses solely on the much-debated Economic Partnership Agreements (EPAs). EPA negotiations date back to the 2000 signing of the Cotonou Partnership Agreement (CPA) between the EU and the African, Caribbean and Pacific states (the ACP group). The ensuing negotiations took a highly controversial contentious turn, culminating during the 2007 EU-Africa Summit, when African heads of state and government accused the EU of looking to conclude trade agree¬ments between fundamentally asymmetrical markets. In light of the upcoming EU-Africa summit in November 2017, it is important to continue the dialogue regarding what the EU and Africa wish to achieve with the EPAs. EPAs could contribute to the strengthening co-operation between the EU and Africa by forming part of a broad strategy supported by adequate political, human and financial resources. EPAs however remain a divisive topic, with many actors having divergent expectations. Yet in spite of ongoing controversy regarding EPAs on both sides, there remains a strong common interest in intensifying trade co-operation between Africa and the EU. Against this background, this paper examines four possible scenarios for the future of the EPAs– with their respective opportunities and risks: Scenario A: Continuing the current EPA strategy Scenario B: Discontinuing EPA negotiations Scenario C: Resuming EPA negotiations on a new basis Scenario D: Pursuing an adapted and more flexible EPA agenda The discussion of these scenarios shows that EPAs offer key benefits to EU-Africa trading relations, for example by strengthening legal security for the parties involved (Scenario A). The discontinuation of negotiations (Scenario B) offers no solution for the future of EU-Africa relations, with a restart of these (Scenario C) also offering little prospect of success. We therefore urge the adoption of a modified and more flexible EPA agenda (Scenario D), which specifically addresses the concerns of the ACP countries, reinforces African regional integration processes, and delivers more supportive measures than a continuation of the current strategy. It is not helpful to consider the EPAs in isolation from the broader field of trade and development and expect them to deliver substantial results on their own. If the current impasse is to be overcome, all actors – whether critical or moderate – need to take part in explicitly interest-led discussions. Scenario D offers the possibility of the EPAs forming an integral element of the debate regarding trade and investment, whereas to date they have formed more of a separate thread of discussion in EU-Africa relations.
Keywords: 330; Handel und Investitionen; Trade and investments